Hard magnet topological semimetals in XPt3 compounds with the harmony of Berry curvature - Markou, Anastasios; Gayles, Jacob; Derunova, Elena; Swekis, Peter; Noky, Jonathan; Zhang, Liguo; Ali, Mazhar N.; Sun, Yan; Felser, Claudia (Communications Physics, 2021)
Topological magnetic semimetals, like Co3Sn2S2 and Co2MnGa, display exotic transport properties, such as large intrinsic anomalous (AHE) due to uncompensated Berry curvature. The highly symmetric XPt3 compounds exhibit anti-crossing gapped nodal lines, a driving mechanism in the intrinsic Berry curvature Hall effects. Uniquely, these compounds contain two sets of gapped nodal lines that harmoniously dominate the Berry curvature in this complex multi band system. We calculate a maximum AHE of 1965 S cm-1 in the CrPt3 by first principles electronic structure. We have grown high-quality CrPt3 thin films with perpendicular magnetic anisotropy by magnetron sputtering and measured a robust AHE of 1750 S cm−1 for different sputtering growth conditions. Additionally, the cubic films display an easy magnetic axis along [111] direction. The facile and scalable fabrication of these materials is prime candidates for integration into topological devices.
CRIS-Team Scopus Importer:2022-04-14